CUPRAC Voltammetric Determination of Antioxidant Capacity in Tea Samples by Using Screen-Printed Microelectrodes - Alina Elena Trofin; Lucia Carmen Trincă; Elena Ungureanu; Adina Mirela Ariton (Journal of Analytical Methods in Chemistry)
Measurement of antioxidant capacity represents an analytical major challenge in terms of accuracy, efficiency, rapid response, or low cost of detection methods. Quantification of antioxidant capacity of food samples using disposable screen‐printed microelectrodes (SPMEs) was based on cyclic voltammetry versus open-circuit potential (CV vs OCP) and differential pulse voltammetry (DPV) as compared with spectrophotometric measurement of the CUPRAC reaction with 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (trolox). The SPMEs are organic‐resistant electrodes and thus compatible with food samples and organic solvents used to dissolve trolox. A micropipette was used to release a drop of 50 μL sample on the spotted surface of the SPME sensor/working electrode that was time programmed to function according to the working protocol. The SPME response was linearly correlated with trolox content. This preliminary demonstration was focused on the analysis of tea infusions, due to the simplicity and reproducibility of the samples’ preparations involved. Analytical results of the antioxidant capacity (expressed as mol·L−1 trolox equivalents) of the tea samples showed a good agreement in the case of spectrophotometry and differential pulse voltammetry (R2 > 0.998). DPV with SPME based on CUPRAC reactions was proven to be a promising approach for the characterization of antioxidant capacity of tea samples with rapid response, cost-effectiveness, and simplicity of operation.